Apoptosis and epicardial contributions act as complementary factors in remodeling of the atrioventricular canal myocardium and atrioventricular conduction patterns in the embryonic chick heart. Issue 9 (28th August 2018) - Vicente Steijn, Rebecca; Sedmera, David; Blom, Nico A.; Jongbloed, Monique; Kvasilova, Alena; Nanka, Ondrej
Abstract : Background : During heart development, it has been hypothesized that apoptosis of atrioventricular canal myocardium and replacement by fibrous tissue derived from the epicardium are imperative to develop a mature atrioventricular conduction. To test this, apoptosis was blocked using an established caspase inhibitor and epicardial growth was delayed using the experimental epicardial inhibition model, both in chick embryonic hearts.Results : Chicken embryonic hearts were either treated with the peptide caspase inhibitor zVAD‐fmk by intrapericardial injection in ovo (ED4) or underwent epicardial inhibition (ED2.5). Spontaneously beating embryonic hearts isolated (ED7–ED8) were then stained with voltage‐sensitive dye Di‐4‐ANEPPS and imaged at 0.5–1 kHz. Apoptotic cells were quantified (ED5–ED7) by whole‐mount LysoTracker Red and anti‐active caspase 3 staining. zVAD‐treated hearts showed a significantly increased proportion of immature (base to apex) activation patterns at ED8, including ventricular activation originating from the right atrioventricular junction, a pattern never observed in control hearts. zVAD‐treated hearts showed decreased numbers of apoptotic cells in the atrioventricular canal myocardium at ED7. Hearts with delayed epicardial outgrowth showed also increased immature activation patterns at ED7.5 and ED8.5. However, the ventricular activation always originated from the left atrioventricular junction. Histological examination showed no changes in apoptosis rates, but a diminished presence of atrioventricular sulcus tissue compared with controls.Conclusions : Apoptosis in the atrioventricular canal myocardium and controlled replacement of this myocardium by epicardially derived HCN4‐/Trop1‐ sulcus tissue are essential determinants of mature ventricular activation pattern. Disruption can lead to persistence of accessory atrioventricular connections, forming a morphological substrate for ventricular pre‐excitation. Developmental Dynamics 247:1033‐1042, 2018 . © 2018 Wiley Periodicals, Inc. Key Findings: Apoptosis is one of the mechanisms in remodeling of the atrioventricular junction. Inhibition of apoptosis results in abnormal myocardial connections and ventricular activation patterns. Epicardial inhibition results in persistence of accessory myocardial atrioventricular connections. Myocyte apoptosis and epicardial invasion are key players in establishment of proper atrioventricular conduction axis.